2019
DOI: 10.1029/2018je005796
|View full text |Cite
|
Sign up to set email alerts
|

The Geology and Astrobiology of McLaughlin Crater, Mars: An Ancient Lacustrine Basin Containing Turbidites, Mudstones, and Serpentinites

Abstract: McLaughlin crater is a 92‐km diameter complex crater that formed on Mars ~4 billion years ago. The resulting basin was the site of a large (~3,000 km2), deep (~500 m), voluminous (~1,500 km3) Martian lake circa 3.8 Ga. While there is strong evidence that hundreds of lakes have existed on Mars at some point during the same time period, the geology of McLaughlin crater is extraordinary for a number of reasons. Detailed spectral analyses show that the deep‐water sediments include detrital inputs of olivine and py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…(2012, 2016) and Michalski et al. (2019). In this model, the least squares fit is constrained to include only positive abundances, as negative mineral abundances have no physical meaning.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…(2012, 2016) and Michalski et al. (2019). In this model, the least squares fit is constrained to include only positive abundances, as negative mineral abundances have no physical meaning.…”
Section: Methodsmentioning
confidence: 96%
“…In this work, we perform spectral mixture analysis of Mars Reconnaissance Orbiter (MRO) Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) visible/near‐infrared (VNIR) hyperspectral imagery over the Jezero deltaic region to estimate abundances of carbonate, olivine, phyllosilicates, and other minerals in the region and to constrain the origins of the lithologies and increase our understanding of how the rocks have been altered through time. Analysis of CRISM imagery is typically limited to feature identification, although recent advances have been made in quantitative unmixing of VNIR hyperspectral imagery using radiative transfer theory (e.g., Edwards & Ehlmann, 2015; Lapotre et al., 2017; Liu et al., 2016, 2012; Michalski et al., 2019) and advanced denoising techniques (Itoh & Parente, 2021). By unmixing single CRISM pixels, we can better understand both the composition of geologic units and their spatial extent.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrihydrite comprises a majority of the X-ray amorphous component in the martian regolith, being present in proportions of up to 50 wt% in mudstones examined at Yellowknife Bay (Dehouck et al, 2017). Ferrihydrite is also found in a wide variety of martian environments, such as in the Rocknest, Cumberland, and Windjana samples as analyzed by CheMin on the MSL Curiosity rover (Bish et al, 2013;Vaniman et al, 2014;Rampe et al, 2016;Treiman et al, 2016;Dehouck et al, 2017), at Gusev Crater and Meridiani Planum as observed by the Mars Exploration Rover missions (Morris et al, 2006a(Morris et al, , 2006b, and other locations such as McLaughlin Crater as observed by the Compact Reconnaissance Imaging Spectrometer for Mars (Michalski et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…More than 400 paleolakes have been identified in previous studies, and they are widely distributed throughout the Martian southern highlands (Cabrol & Grin, , ; De Hon, ; Fassett & Head, ; Goudge, Head, et al, , Goudge, Aureli, et al, ; Newsom et al, ). Paleolakes are windows to the regional geologic history and climatic evolution of ancient Mars (Cabrol & Grin, ; Eigenbrode et al, ; Forsythe & Blackwelder, ; Fukushi et al, ; Goldspiel & Squyres, ; Grotzinger et al, ; Irwin et al, ; Michalski et al, ): Their morphology and distribution can reflect the distribution of water, the compositions of lake deposits are indicators of hydrologic and climatic conditions, and resurfacing landforms in the lake basins can record later geologic processes and climate changes. Therefore, paleolakes have long been suggested as candidate landing sites for Martian in situ exploration missions (Grant et al, ; Grin & Cabrol, ; Haskin et al, ; Wray, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies mostly focused on the global identification and distribution of paleolakes (Cabrol & Grin, , ; De Hon, ; Fassett & Head, ; Goudge, Head, et al, ; Goudge, Aureli, et al, ) or detailed analyses of a single paleolake (Cabrol et al, ; Dehouck et al, ; Glotch & Christensen, ; Goudge, Mustard, et al, ; Grin & Cabrol, ; Irwin et al, ; Irwin et al, ; Michalski et al, ; Palucis et al, ; Pajola et al, ; Salvatore et al, ); nevertheless, identification and comprehensive analyses of paleolakes at regional scales are also of great significance for understanding the geologic and climatic history of an area. In this study, we chose the area located around the northwest margin of the Hellas basin as our study region (40°–65°E, 15°–35°S; Figure ).…”
Section: Introductionmentioning
confidence: 99%